A report on VR Headset and its effects on children - Aya Saudi (Cybrarians Journal, 2021)
Virtual Reality is a word that we find that explains itself in a simple way about the meaning of the technology, which is watching a surrounding world around you that does not actually exist, and we can say that it is a three-dimensional imaginary world with sound and image, and makes you get the same sensation as if you were inside this world to live an experience whether excitement, horror or psychological calm, and many believe that virtual reality technology is new, but this technology dates back to 1960 under the name "Head sight", and it was working purely mechanically with no viewing technology. Not only that, but the idea appeared 200 years ago with different methods of implementation and its difficulty at this time, and the general trend was to employ this technology to serve the military side, training pilots and also in the medical field, which is indeed what is happening now, but we find that the commercialisation of this technology was through the creation of many games and videos that greatly support it, and are continuously developed, so we find some believe that virtual reality technology is intended for entertainment only, but this is not actually the truth, as I mentioned earlier. Recently, the world has witnessed a wide spread of the technology of VR gaming glasses for children, and this technology came to be the natural and expected alternative to using the computer screen or mobile phone, and this technology simply displays everything that the child sees on the screen by using glasses dedicated to this purpose, by connecting it to the PC or installing the mobile phone inside the glasses